The Seminal Contribution of Rabbi Moshe Feinstein to the Development of Modern Jewish Medical Ethics - Jotkowitz, Alan (Journal of religious ethics, 2014)
The purpose of this essay is to show how, on a wide variety of issues, Rabbi Moshe Feinstein broke new ground with the established Orthodox rabbinic consensus and blazed a new trail in Jewish medical ethics. Rabbi Feinstein took power away from the rabbis and let patients decide their treatment, he opened the door for a Jewish approach to palliative care, he supported the use of new technologies to aid in reproduction, he endorsed altruistic living organ donation and recognized brain death (thus laying the groundwork for Orthodox Jewish acceptance of heart transplantation), he downplayed the value of social worth in triage decisions, and was a fierce defender of the rights of the fetus. I develop broader theological principles from Rabbi Feinstein's ethical positions and compare them to those of his Jewish and Christian contemporaries.